2020
DOI: 10.1021/acs.joc.0c02582
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed One-Pot Access to N-Polycyclic Aromatic Hydrocarbons from Aryl Ketones through Triple C–H Bond Activations

Abstract: A Rh-catalyzed pot and step economic synthesis of aza-polycyclic aromatic hydrocarbons (N-PAHs) from readily available aryl ketones and alkynes has been disclosed. Additionally, a novel synthetic application of the well-known aminating reagent hydroxylamine-O-sulfonic acid (HOSA) has been explored as an in situ redox-neutral directing group for the formation of N-PAHs via isoquinoline. Multiple bond formation in a single operation through a cascade of triple C−H bond activations is the beauty of this protocol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The N1–C1–C13 angle (120.9(3)°) in 6-methyl-substituted 2i-Au(OAc F ) 2 is slightly larger than the corresponding N–C–C(alkyl) angles in reported crystal structures of non-coordinated pyridines, bipyridines or phenanthrolines with alkyl substituents α to nitrogen (typically around 115°). 89–93 This indicates that Au( iii ) coordination to 6-methyl-substituted pyridines results in a widening of the N–C–C(methyl) angle, contrary to the effect Au( iii ) coordination has on the N–C–O(methoxy) angle in 6-methoxy-substituted pyridines. The N–C–C(alkyl) angle in 2i-Au(OAc F ) 2 is similar to reported angles for related square planar Au( iii ) 94 and Pd( ii ) 58 complexes of 6-methyl-substituted (bi)pyridine ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The N1–C1–C13 angle (120.9(3)°) in 6-methyl-substituted 2i-Au(OAc F ) 2 is slightly larger than the corresponding N–C–C(alkyl) angles in reported crystal structures of non-coordinated pyridines, bipyridines or phenanthrolines with alkyl substituents α to nitrogen (typically around 115°). 89–93 This indicates that Au( iii ) coordination to 6-methyl-substituted pyridines results in a widening of the N–C–C(methyl) angle, contrary to the effect Au( iii ) coordination has on the N–C–O(methoxy) angle in 6-methoxy-substituted pyridines. The N–C–C(alkyl) angle in 2i-Au(OAc F ) 2 is similar to reported angles for related square planar Au( iii ) 94 and Pd( ii ) 58 complexes of 6-methyl-substituted (bi)pyridine ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Following their work on the application of hydroxylamine- O -sulfonic acid to form isoquinolines, Ravikumar et al recently reported the synthesis of aza-polycyclic aromatic hydrocarbons 62 via triple C–H bond activation of aryl ketones 61 and internal alkynes 63 (Scheme 22). 33 This Rh( iii )-catalysed transformation also demonstrated the annulation of two different alkynes in a regioselective manner. The substrate scope for this reaction was generalised with a wide range of substituents.…”
Section: Various Transition Metal-catalysed Annulation Reactions Of A...mentioning
confidence: 90%
“…The scope of benzophenones was also vast, and most of the substitutions were tolerated successfully. 33 This Rh(III)-catalyzed transformation also demonstrated the annulation of two different alkynes in a regioselective manner. The substrate scope for this reaction was generalized with a wide range of substituents.…”
Section: Scheme 16 Rhodium Catalyzed Carboxylate-directed C-h Functio...mentioning
confidence: 91%